ANALYSIS OF THE IMPACT OF FINANCIAL PERFORMANCE (ENVIRONMENTAL, SOCIAL, GOVERNANCE) ON COMPANY INVESTMENT RISK - Jabida Latuamury; Kathleen Asyera Risakotta; Theresia Febiengry Sitanala (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The impact of financial performance on a company's investment risk can be very significant. Poor financial performance can cause various risks for a company, including a decline in share value, risk of bankruptcy, and even forced delisting from the stock exchange. Poor financial performance can adversely affect the value of the company. Good financial performance can help increase a company's value and profitability. Effective financial risk management can help Businesses recognize, quantify, and handle risks associated with their financial performance, thereby minimizing their negative impact. ESG is an important factor in business and investment because it helps companies manage risk, build reputation and create favorable effects on society and the environment. A deeper understanding of this concept is key to ensuring that companies and investors can contribute to a more sustainable world. This research in-depth investigates the analysis of the use of the literature research approach to examine how financial performance (environmental, social, and governance) affects the investment risk of a corporation. The definition of financial, environmental, social, and governance performance is covered in this study, along with how financial performance affects firm investment risk and how environmental, social, and governance factors influence financial performance.